(untitled) (CAHIERS MAGELLANES-NS, 2024)
This review aims at exploring green cleaning practices in hotel housekeeping with emphasis on the practices, advantages, and disadvantages. The literature review was conducted using the databases PubMed, Scopus, Web of Science, and Google Scholar using keywords such as “green cleaning practices,” “hotel housekeeping,” and “sustainability in hospitality” and yielded articles. These articles were chosen because they are peer-reviewed and published within the last 20 years, thus, containing relevant information. Data were categorized into four main themes: Green Cleaning: Benefits, which include environmental enhancement, cost reduction, and staff and guests’ health; Implementation Barriers, which include cost, staff training, and resistance; Green Cleaning Best Practices, which outlines the best practices for green cleaning; and Case Studies, which presents successful green cleaning implementation in hotels. The analysis of the qualitative content provided patterns and insights such as [particular trends or issues]. This paper presents a literature review of the current state of green cleaning in hotels and presents best practices and suggestions for improving sustainability and productivity in hotel housekeeping.